Potential of Red Spinach Leaves Ethanolic Extract (Amaranthus tricolor L.) as a Complementary Therapy For Hiperlipidemia: Study in Vivo of Histopathologic and Activity of Alanin Aminotransferase (ALT) - Dimas Adhi Pradana; Irna Destya Anggriani; Tri Ratna Setyaningrum (Jurnal Sains Farmasi & Klinis, 2016)
This study was conducted to determine the potential of ethanolic extract of red spinach leaves (Amaranthus tricolor L.) with control quality as a complementary treatment of hyperlipidemic based on histopathology and activity of alanin aminotrasferase (ALT). A total of 24 male Wistar rats were randomized in 6 groups: normal group; positive control group were given the drug simvastatin; negative control group; 1st treatment group was given extract at dose of 400mg/kgBW rat, 2nd group was given extract at dose of 400mg/kgBW rat and simvastatin dose 0.18 mg/kgBW rat; 3rd treatment groups were given extract at dose of 800mg/kgBW rat and simvastatin dose 0.18 mg/kgBW rat. Induction hyperlipidemic using high fat diet and poloxamer. The data obtained were tested normality with the Shapiro-Wilk test. Statistical analysis using Oneway ANOVA and Post-Hoc Tukey HSD to determine the significance of differences between groups for ALT parameter. Result show the use of ethanolic extract of red spinach leaves can reduce fatty liver condition based on decreased level of ALT and liver histopathologic. It is concluded that the ethanolic extract of red spinach leaves dose 400mg/kgBW rat combine with simvastatin can reduce activity of ALT until 31.57 U1-1.